Pulmonary metastasectomy: what is the practice and where is the evidence for effectiveness? - Treasure, Tom (BMJ Publishing Group, 2014)
Pulmonary metastasectomy is a commonly performed operation and is tending to increase as part of a concept of personalised treatment for advanced cancer. There have been no randomised trials; belief in effectiveness of metastasectomy is based on registry data and surgical follow-up studies. These retrospective series are comprised predominately of solitary or few metastases with primary resection to metastasectomy intervals longer than 2–3 years. Five-year survival rates of 30–50% are recorded, but as case selection is based on favourable prognostic features, an apparent association between metastasectomy and survival cannot be interpreted as causation. Cancers for which lung metastasectomy is used are considered in four pathological groups. In non-seminomatous germ cell tumour, for which chemotherapy is highly effective, excision of residual pulmonary disease guides future treatment and in particular allows an informed decisions as to further chemotherapy. Sarcoma metastasises predominately to lung and pulmonary metastasectomy for both bone and soft tissues sarcoma is routinely considered as a treatment option but without randomised data. The commonest circumstance for lung and liver metastasectomy is colorectal cancer. Repeated resections and ablations are commonplace but without evidence of effectiveness for either. For melanoma, results are particularly poor, but lung metastases are resected when no other treatment options are available. In this review, the available evidence is considered and the conclusion reached is that in the absence of randomised trials there is uncertainty about effectiveness. A randomised controlled trial, Pulmonary Metastasectomy in Colorectal Cancer (PulMiCC), is in progress and randomised trials in sarcoma seem warranted.